Psychometric properties of the Five-executive Function Tests in Indonesian samples - Wulanyani, Ni Made Swasti; Widhianingtanti, Lucia Trisni; Immanuel, Aria Saloka; Aisyah, Aireen Rhammy Kinara; Hendriks, Marc P. H.; Hestyanti, Yohana Ratrin; Suryani, Angela Oktavia; van Luijtelaar, Gilles (Psikohumaniora: Jurnal Penelitian Psikologi, 2024)
Difficulties in executive function (EF) may be causative factors in clinical conditions, including learning disabilities, depression, and anxiety. However, defining the structure of EF is an ongoing issue, although Miyake’s three-factor structure is widely accepted. This study aims to discover the underlying factor structure of EF domains, as measured by five tests and the scores of 840 participants, to establish the domains’ validity and reliability. Five neuropsychological tests were included in the exploratory and confirmatory factor analyses (EFA and CFA): the Digit Span (DS); the Stroop Color Word Test (Stroop Test); the phonemic Verbal Fluency Test (pVFT); the Five Point Test (5PT); and the Trail Making Test (TMT). EFA could be meaningfully performed (KMO = .862, Bartlett’s test: ????2 =1393.169, df 45, p < .001) and yielded three factors closely mirroring the three core domains of EF. CFA of the model in which the 5PT loaded on factor 2 showed the best goodness of fit indicators, although the difference with the other three-factor models was small. Currently, these EF tests are available in Indonesia and suitable for use, although obtaining normative scores adjusted for demographic factors is necessary.